Proses Kognitif pada Neologisme Ciptaan Bunga Reyza - Lita Nur Azila (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
A neologism is a new term or concept that emerges to meet a communication need. In practice, neologisms can take various forms and are created through a variety of cognitive processes. One influencer who clearly illustrates the role of cognitive processes in the creation of neologisms is Bunga Reyza. This research aims to examine (1) the form of the neologisms created by Bunga Reyza in accordance with the theory of Zabotkina and Lee, as formulated by Satriani, and (2) the cognitive processes involved in their creation, referencing Stekauer’s Onomasiological model. This research employs a qualitative, descriptive research design. The research data consists of Bunga Reyza’s utterances containing the neologisms she created. The data were obtained from (1) TikTok videos by Bunga Reyza containing spoken utterances regarding the new words she created and (2) TikTok comment sections in the form of conversations containing responses and the reuse of Bunga Reyza’s newly created words by netizens to verify the status of the neologisms. The data collection technique used in this research is documentation. The data analysis technique employs the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions and verification. The results of the research show that the neologisms created by Bunga Reyza take the form of new word forms or new words. Regarding the cognitive process, the sequence of stages in the creation of neologisms by Bunga Reyza exhibits characteristics that differ slightly from Stekauer’s onymatological model. Neologisms by Bunga Reyza tend to be created spontaneously or emphasize the perceived suitability of sound to the meaning they represent.
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: Cognitive processes; forms of neologisms; neologisms; Onomasiological Model